TRANSMETACARPAL REPLANTATION. ELEVEN YEARS LATER - Binka Popova; Elena Mateva; Kevork Kaykchian; Deyan Sokolov (Journal of the Bulgarian Orthopaedics and Trauma Association)
A case in a series of nine transmetacarpal replantations was presented at the combined meeting of the 7th European congress on Prevention of Hand Traumas and the 7th congress of the Bulgarian Society for Surgery of the Hand, 19-21 October 2023, Plovdiv, Bulgaria.